Sub-bacias hidrográficas do Alto Jaguaribe (Tauá-CE): vulnerabilidades ante a incidência de degradação / desertificação - Pinheiro, Rosângela Maria Paixão (2003)
Since the origins of civilization, natural elements of river basins – water, soil, vegetation, among others – are used in human activities to meet man’s needs. Among them, water is such an important resource that its shortage can influence the development of a region and can cause socioeconomic problems, a problem existing in the semi-arid area of Brazil. The area of the present study – a high valley of Jaguaribe river basin – has a seasonal water unavailability caused by the low annual rainfall rates (550– 650 mm/year), high temperatures (25oC to 28oC) great evaporation rates (119 to 307 mm), which produce a water deficit. This area is also characterized by a the limited potential of other natural resources, among them - shallow soils (Lithic Nessolos, Luvissolos and Neossolos Flúvios) and complex open vegetable formation open (caatinga), which in drought periods are intensified. As a result, the population is subjected to the situation of socioeconomic poverty and environmental vulnerability, producing a susceptibility to desertification. In this context, the present work aims to develop a geoenvironmental analysis in sub river basins in Tauá Town, Ceará State, Brazil by characterizing and classifying those basins according to hydrodynamic conditions, expressing vulnerability scenarios in order to enable the sustainability of its natural resources. The methodology consisted of integrating the quantitative analysis of the drainage net with the qualitative approach in systemic perspective about the physical-environmental and socioeconomic components. We applied parameters and concepts based on HORTON (1945), STRAHLER (1952, among others mentioned by CHRISTOFOLETTI (1980);BERTALANFY (1932), BERTRAND (1972); cartographic bases of SUDENE/ASMIC (1967), SUDENE (1973) and WAVES (2001). In the results obtained concerning the hydrodynamic characteristics, the sub-basins of the brooks Carrapateiras and Catumbi presented more complex hierarchies (4th order), than the sub-basins of the brooks Cipó and Trici (3rd order). The analyses of the morphometric indexes enhances the characterization of the sub-basins in relation to the larger or smaller predisposition to erosion processes and other hydrological dynamics. Therefore, the parameters of shape index (Ff, Kc and “C”), made the author classify all the sub-basins with an irregular shape, favoring the proper time for formation of runoff. This dynamics was also expressed by the “Cmc” and “Eps” indexes – average length of canals and runoff. The first one evidenced in almost all the sub-basins, except for Catumbi, the search for the proper adjustment of the canals, through which the largest average length is to the canals of 1st order, with reduction of the average course for highest orders. In the second index, the sub-basins of Catumbi and Cipó – 0.86 km and 0.81 km respectively – presented indicators more pronounced to the erosion processes than the subbasins of Carrapateiras and Trici, with 0.78 km and 0.76 km, respectively. In the river and drainage densities – “Dr” “Dd” – the results for Cipó, Carrapateiras, Trici and Catumbi brooks, for each index, respectively, were: 0.1 c/km, 0.08 c/km, 0.14 c/km, 0.21 c/km and 0.61km/km2, 0.64 km/km2, 0.65 km/km2, 0.58 km/km2; indicating low frequency of canals and the low pattern of drainage per pattern area, representing a balance between runoff and infiltration. This dynamics was also analyzed in the set composed of average slope roughness coefficient – “D” “Rg” – which in the sub-basins of Carrapateiras and Trici expressed a better balance by the results – 8.09%, 5.10% and 5.17%; 3.31 for each index respectively; concerning the sub-basins of Catumbi and Cipó, respectively, with, 3.96%, 4.20% and 2.29%; 2.56%. The socio-environmental analysis evidenced unharmonious relationships, established in the areas covered by the sub river basins because of the economic structure and through soil use during approximately five (5) centuries of exploitation of natural resources. In the division of the river sub basins in geoenvironmental units and sub-units, there was a predominance, with relation to the smallest and largest geoenvironmental variation, respectively, of the sub-basins of Cipó brook (3 units and 5 sub-units) and Carrapateiras (5 units and 18 sub-units), and that also emphasize the more pronounced natural vulnerabilities. While the sub-basins of the brooks Trici and Catumbi (both with 4 units and 12 sub-units) stood out through the conditions of greater interaction and preservation of the physical-environmental components, resulting in lower natural vulnerabilities. In almost all of the sub-basins, we identified the relative occupation by the unit Z3 - areas partially dissected, except for the brook Catumbi, which is relatively occupied by the unit Z2 - flat to dissected areas. Evidencing that, as the geologicalgeomorphological time goes by, the sub-basins go through intense denudation process. The analyses conducted allowed the author to classify the river sub-basins into the following categories: high environmental vulnerability for Cipó brook; medium to high environmental vulnerability for Carrapateiras brook; medium environmental vulnerability for Trici brook, and medium to low environmental vulnerability for Catumbi brook. Therefore, we conclude that the environmental conditions in the river sub-basins express a group of phenomena with strong antagonism, between the hydrodynamic and physical-environmental balance for the semi-arid area, with the socioeconomic dynamics of the exploitation of natural resources. They are revealed through strong negative environmental changes, resulting in phenomena that stimulate the natural environmental vulnerabilities, and that are related to the degradation/desertification in the river sub-basins in the high Jaguaribe river in Tauá town, CE.